Genetic diversity among natural populations of Schistosoma haematobium might contribute to inconsistent virulence and diverse clinical outcomes. Issue 4 (December 2016) - Afifi, Mohammed A.; Jiman-Fatani, Asif A.; Al-Hussainy, Nabeel H.; Al-Rabia, Mohammed W.; Bogari, Anas A.
Abstract: There is an evident difference in the intensity of morbidity caused by Schistosoma haematobium in North-African zones compared to Sub-Saharan ones. Clinical outcome dichotomy corresponds to two geographically distinct intermediate host snail species that are only infected by the related strain of the parasite. In concert, there is a manifest hybridization of the parasite with other Schistosoma species confined to certain regions of Africa. This raises a reasonable suggestion that S. haematobium has no less than two phylogenetic clusters that have different virulence. The aim of the study was to examine the possible diversity among S. haematobium using simultaneous amplification of genomic DNA of selected isolates. Random amplified polymorphic DNA-polymerase chain reaction markers were used to study the genetic diversity among S. haematobium natural isolates from selected regions of Africa (Egypt, Zimbabwe, and South Africa) that represent different ecological conditions, different species of intermediate host, and different possibilities of field hybridization with other schistosomes. A moderate to high level of genetic diversity was evident among the three isolates. More bands were shared by the isolates from Zimbabwe and South Africa (similarity index = 0.721) than those shared by each with the Egyptian isolate (similarity index = 0.551 and 0.566, respectively), suggesting that at least two phylogenetic groups of S. haematobium do exist in distinct geographic regions of Africa. The elucidation of the possible genetic diversity among S. haematobium parasites may explain many ambiguous aspects of the biology of the parasite-like virulence, immune evasion and drug resistance.